Biological Activity of Extracts from Some Species of Coniferous Plants - Elisovetcaia, Dina Stepan; Ivanova, Raisa; Gladei, Diana; Simkova, Jana; Brindza, Jan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The development and use of biological preparations based on plant secondary metabolites is an important trend in modern organic farming. Among secondary metabolites, a significant place is belong to substances of the class of terpenoids (isoprenoids), which possess a wide spectrum of biological activity and practically no toxicity to warm-blooded animals and humans. One of the main sources of terpenoids is conifers, such as Juniperus sabina L. (Cupressaceae) and Pinus sylvestris L. (Pinaceae), which in quantitative content and qualitative composition are vastly superior to other widely distributed species in the plant world. Thus, the secondary metabolites of savin juniper and scots pines advantageous as a raw material for the production of various biological preparations for organic agriculture. The aim of this study was to determine the biological activity of extracts and essential oils from species of Juniperus sabina and Pinus sylvestris, growing in the Republic of Moldova (RM) and Slovak Republic, Nitra (SN) and Pianiny mountains (PM). The antioxidant activity of ethanolic extracts of Coniferous was determined by two procedures with appreciation of their radical scavenging capacities against DPPH and peroxyl free radicals and was evaluated in equivalent of standard substances (Trolox and gallic acid) and by indexes IC50. According to the determined indexes the antioxidant activity of tested extracts from Coniferous plants was qualified in followed order: J. sabina SN ˃ J. sabina PM ˃ J. sabina RM˃ P. sylvestris RM ≥ P. sylvestris SN. Moreover, it was established that both ethanolic extracts and essential oil J. sabina possessed high efficiency against Leptinotarsa decemlineata Say and Galleria mellonella L. Mortality of imago and larvae consisted in average 6.7–53.3 and 66.7–100 % respectively, ovicidal activity was 100 %, and antifeedant effect persisted at the level of 1–3 points. The treatment of feed and insects with the essential oils of P. sylvestris needles resulted in the death of only 6.7–13.3 % of the wax moth larvae.